Crystal structure of bis(μ2-2-(1,5-dimethyl–3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl)imino)methyl)phenolato-κ4O:O,N,O′)-(nitrato-κ2O,O′)dicobalt(II), C36H32Co2N8O4 - Tian Jiaze; Miao Siyi; Wan Xin; Mou Jin; Zhang Zhenchang; Tang Qiang; Pang Haixia (Zeitschrift für Kristallographie - New Crystal Structures)
C36H32Co2N8O4, monoclinic, P21/c (no. 14), a = 12.2971(12) Å, b = 13.1008(13) Å, c = 11.0864(11) Å, β = 99.174(2)°, V = 1763.2(3) Å3, Z = 2, Rgt(F) = 0.0277, wRref(F2) = 0.0818, T = 296 K.